Pesticide Exposure to Liver Function of Farmers in Rural and Remote Areas in Indonesia: A Correlational Study - Rafi'ah Rafi'ah; Iga Maliga; Gladeva Yugi Antari (Saintika Medika, 2022)
Farmers are exposed to pesticides that impact liver function disorders, especially during the pesticide spraying process. Several studies have shown that there is a link between liver damage associated with pesticide use. This study aims to compare the intensity of pesticide exposure to the liver function disorders of farmers. Farmers in this study were divided into two groups, namely farmers in rural areas and remote areas. This study is a quantitative descriptive study with a cross-sectional study approach. This research was conducted in April - August 2020 in Indonesia, involving 40 farmer respondents from rural and remote areas in Sumbawa Regency, Indonesia. The results show that chi-square table values of length of time working as farmers, a spraying method, and smoking habits less than chi-square calculated so that they are no correlations with the highest amount of S.G.O.T. and S.G.P.T. The chi-square value shows a relationship between the use of P.P.E. with A.S.T. levels but not with the S.G.P.T. value. The S.G.P.T. value in both groups indicates a relationship between the S.G.P.T. level and P.P.E. because of the Chi-Square table value <the calculated Chi-Square value. The results showed that the length of time working as a farmer, spraying method, and smoking habits had no correlation with high levels of S.G.O.T. and S.G.P.T. among farmers in rural and remote areas. Then the use of P.P.E. that is not right affects the levels of S.G.O.T. and S.G.P.T. in farmers.